Singlet‐Oxygen‐Induced Phospholipase A2 Inhibition: A Major Role for Interfacial Tryptophan Dioxidation. Issue 59 (15th September 2021) - Nasri, Zahra; Memari, Seyedali; Wenske, Sebastian; Clemen, Ramona; Martens, Ulrike; Delcea, Mihaela; Bekeschus, Sander; Weltmann, Klaus‐Dieter; von Woedtke, Thomas; Wende, Kristian
Abstract: Several studies have revealed that various diseases such as cancer have been associated with elevated phospholipase A2 (PLA2 ) activity. Therefore, the regulation of PLA2 catalytic activity is undoubtedly vital. In this study, effective inactivation of PLA2 due to reactive species produced from cold physical plasma as a source to model oxidative stress is reported. We found singlet oxygen to be the most relevant active agent in PLA2 inhibition. A more detailed analysis of the plasma‐treated PLA2 identified tryptophan 128 as a hot spot, rich in double oxidation. The significant dioxidation of this interfacial tryptophan resulted in an N‐formylkynurenine product via the oxidative opening of the tryptophan indole ring. Molecular dynamics simulation indicated that the efficient interactions between the tryptophan residue and phospholipids are eliminated following tryptophan dioxidation. As interfacial tryptophan residues are predominantly involved in the attaching of membrane enzymes to the bilayers, tryptophan dioxidation and indole ring opening leads to the loss of essential interactions for enzyme binding and, consequently, enzyme inactivation. Abstract : We showed that singlet oxygen produced from cold physical plasma efficiently inactivated the PLA2 enzyme. Experimental and computational analysis proved that the dioxidation of interfacial tryptophan residue to N‐formylkynurenine led to the decay of appropriate interactions between the enzyme and phospholipid, which prevented the enzyme attachment to the membrane consequently inhibited the enzyme efficiently.